Neural Basis of Etiopathogenesis and Treatment of Cervicogenic Orofacial Pain - Šedý, Jiří; Rocabado, Mariano; Olate, Leonardo Enrique; Vlna, Marek; Žižka, Radovan (Medicina (Kaunas, Lithuania), 2022)
(1) Background and Objectives: The aim of this narrative review was to analyze the neuroanatomical and neurophysiological basis of cervicogenic pain in cervico-cranial pain syndromes, focusing particularly on cervico-orofacial syndromes as a background for the proper diagnosis and non-surgical treatment. Relevant literature on the topic from past 120 years has been surveyed. (2) Material and Methods: We surveyed all original papers, reviews, or short communications published in the English, Spanish, Czech or Slovak languages from 1900 to 2020 in major journals. (3) Results: The cervicogenic headache originates from the spinal trigeminal nucleus where axons from the C1-C3 cervical spinal nerves and three branches of the trigeminal nerve converge (trigeminocervical convergence) at the interneurons that mediate cranio-cervical nociceptive interactions. The role of the temporomandibular joint in the broad clinical picture is also important. Despite abundant available experimental and clinical data, cervicogenic orofacial pain may be challenging to diagnose and treat. Crucial non-surgical therapeutic approach is the orthopedic manual therapy focused on correction of body posture, proper alignment of cervical vertebra and restoration of normal function of temporomandibular joint and occlusion. In addition, two novel concepts for the functional synthesis of cervico-cranial interactions are the tricentric concept of mouth sensorimotor control and the concept of a cervicogenic origin of bruxism. (4) Conclusions: Understanding the basis of neuroanatomical and neurophysiological neuromuscular relations enables an effective therapeutic approach based principally on orthopedic manual and dental occlusal treatment.
Keywords: Cervical Vertebrae; posture; pain; postura těla; krční obratle; Facial Pain; physiotherapy; Posture; cervicogenic; temporomandibular joint; lidé; Surveys and Questionnaires; obličejová bolest; Humans; průzkumy a dotazníky